Alternative approach to design matching network for differential drive rectifier used in RF energy harvesting. (December 2016) - Chouhan, Shailesh Singh; Halonen, Kari
Abstract: In this work, a measurement-based technique to determine LC-matching network for RF-to-DC converter is proposed. It is shown that the differential drive rectifier can be configured as the differential CMOS LC-oscillator by swapping input and output terminals. Thus, this oscillator can then be used to find the inductor (L) and capacitor (C) component values for the rectifier matching network at the intended frequency, which is the oscillation frequency of the oscillator. Measured results show that the absolute frequency error between resonant frequency obtained from oscillator mode and matching frequency obtained as rectifier is less than 2%. The switching core used in this work has been implemented in a standard 0.18 μm CMOS technology and external discrete passive components are used to form the LC network.